Investigation of the Effect of Virtual Manipulatives Usage on the Process of Eliminating Misconceptions about Algebraic Expressions and Equations - Tuğba Temür; Eyüp Sevimli (Uluslararası Türk Eğitim Bilimleri Dergisi)
In this study, the effect of activity-based mathematics content enriched with virtual manipulatives on the process of eliminating misconceptions about algebraic expressions and equations was examined. The virtual manipulative, developed by the researchers and examined for its effects, was also evaluated in terms of suitability for student needs regarding algebraic expressions and equations and compatibility with program achievements. In this research, a pretest-posttest control group quasi-experimental design was used. The study group of the research consisted of a total of 60 students studying at the 7th grade level in a public school. In the experimental group, virtual manipulatives developed by the researchers were used, and in the control group, activities in the current secondary school mathematics textbook were used to explain algebraic expressions and equations. Testing was used to determine misconceptions, and interview techniques were used to describe the effectiveness of the teaching process. The study results showed that activity-based teaching practices applied in both the experimental and control groups were effective in eliminating initial misconceptions. In the teaching of the experimental group, the order of operations and the representation of algebraic expressions, it was determined that the teaching in the control group was more useful in terms of eliminating misconceptions about the relationships between letters and objects. The results regarding the post-test scores showed that there was a statistically significant difference in favor of the experimental group compared to the control group in terms of eliminating misconceptions. Suggestions for the effective use of virtual manipulatives more in mathematics teaching are discussed.